The ontogeny of two species of the family Notodromadidae (Cypridoidea, Ostracoda, Crustacea); taxonomic and palaeogeographic significance - Smith, Robin James; Deckker, Patrick De; Kamiya, Takahiro (Zootaxa, 2022)
Details of the post-embryonic development of two Notodromadidae species, Notodromas trulla Smith & Kamiya, 2014 and Newnhamia fenestrata King, 1855, (subfamily Notodromadinae) are provided, and compared with previous ontogenetic studies on other podocopid families and superfamilies. The ontogenetic development is generally similar to other families, consisting of eight free-living juvenile stages and one adult stage, but the first instar, with a leg-like mandible, resembles that of the Cyprididae, rather than other families. From the A-7 instar onwards, the ventral margin of the carapace is a flattened ovoid, and the dorsolateral eye cups are separated, resembling those of the adults, suggesting that a neustonic lifestyle, similar to that of the adults, is embraced from a very early age. In addition to the ventral margin, other apomorphies of the Notodromadinae include spur-like protrusions on the walking legs of juveniles, which become reduced in adults, and features of the mandibles, probably related to neustonic feeding. Overall, Ne. fenestrata has more plesiomorphic features than No. trulla, and most differences between the two species are related to sexually selected characters, such as different sexually dimorphic features of the antennae. This suggests that sexual selection has been the main evolutionary driving force causing morphological divergence in the subfamily. The two taxa, one from Japan (No. trulla), the other Australia (Ne. fenestrata), have perhaps been separated since the breakup of Pangaea, which started in the Middle Jurassic. This suggests that despite the long geographical isolation, many aspects of ostracod anatomy have remained unchanged over long periods of time. On reviewing the taxonomy of the family, we conclude that monophyly needs to be confirmed with further work, and the subfamily Notodromadinae can be divided into two groups: the Notodromas-group and the Newnhamia-group.